Assessing the future prospects of solar energy conversion technologies in electronic applications - Maha Abdul ameer Kadhim, Dr (International Journal of Engineering and Technology, 2018)
Solar energy has become one of the most important sources of renewable energy. This is evident in the fact that many organizations and individuals have resorted to renewable energy, without fear of depletion, without fear of the monthly costs of using fuel-based electricity.The study examined the mechanism of using solar energy and the mechanism of solar cells in converting sunlight into electricity in general, and thus allocating research in solar energy conversion technologies to electrical energy, and some systems of assessing of these technologies, in order to know the future status of the technology of converting solar energy, as well as to know the costs that these technologies must reach in order to be a candidate for bulk power.Â Â